POST-HYPOXIC DYSFUNCTION OF CARDIOVASCULAR SYSTEM IN NEWBORN CHILDREN - M.V. Narogan; L.K. Bazhenova; E.I. Kapranova; N.A. Mel'nikova; N.A. Belousova ("Paediatrician" Publishers LLC, 2007)
The article discusses the condition of cardiovascular system in the newborn children with medium and heavy hypoxic affection of the central nervous system. High frequency of post hypoxic cardiovascular dysfunctions in this segment of children is shown. The article characterizes the clinical, electrocardiographic and echocardiographic parameters of post hypoxic changes to the cardiovascular system, the acuteness of which depends on the extent of the central nervous system affection. The article describes the favorable course of post hypoxic car diodysfunctions which are to be gradually leveled off in the 1st six months of life on the complex treatment background.Key words: newborn children, perinatal affection of the central nervous system, post hypoxic cardiovascular dysfunctions.